STRATEGI PEMASARAN FIBRE DI PT. POLYSINDO EKA PERKASA KARAWANG MARKETING STRATEGY AT PT. POLYSINDO EKA PERKASA KARAWANG - BANUARA NADEAK (Jurnal Politikom Indonesiana, 2017)
ABSTRACT In leading the market PT. Polysindo Eka Perkasa always ensuring quality, competitive prices,excellent service and reliability. This can be shown by production results in 1996 amounted to137,956,343.6 kg and compared with 2001 amounted to 140,964,592.1 kg.Knives analysis resultsby SWOT, use Internal Factors Analysis Summary (IFAS), that the total value of strength factor1,90 and a total value of weakness 1,70. With the basis this analysis, the value of IFAS matrix0,20. While Eksternal Factors Analysis Summary (EFAS) shown the total value of opportunityfactor 1,65 and threat factor 2,10. So by analysis the value of EFAS matrix -0,45 therefore bySWOT analysis diagram at quadrant 2 using by diservikasi strategy with develop quality andcompetitive price competition with the long-term and do corporate (MOU) with the long-term bytransport fleet in order to distribute on time. The results of the distribution made fiber productionsafety triangle with associated components is the Marketing Manager, Production Planning andControl Components Control Quality of the distribution of the goods on target. Key words : Marketing Strategy, Quality Control, Standar Value of Sales